Dampak Inflasi terhadap Pola Konsumsi Rumah Tangga di Kota Kupang - Freitas, Libania Maria Ferreira; Mau, Yuliana; Amaral, Casimira Ketlin; Lawalu, Emiliana Martuti (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Inflation presents a persistent economic challenge, particularly in developing urban areas such as Kupang City, Indonesia. It directly affects household consumption patterns by reducing purchasing power and forcing families to reprioritize their spending. This study aims to analyze the impact of inflation on household expenditure in Kupang and to identify adaptive strategies employed by households in response to rising prices. A mixed-methods approach was used, employing an explanatory sequential design. Quantitative data were collected from 100 households through structured surveys, while qualitative data were gathered via in-depth interviews with eight participants from various socioeconomic backgrounds during May–June 2025. The results indicate significant increases in essential spending, especially on food and transportation, accompanied by reductions in recreational expenses and savings. Interview findings revealed that households coped with inflation by cutting non-essential expenditures and adjusting lifestyle choices. These insights highlight the importance of understanding localized household behavior and can inform more targeted and responsive economic policies to support vulnerable communities in times of economic stress.